Identifcation of quantitative trait loci for salinity tolerance in rice (Oryza sativa L.) through Sahel 328/NERICA‑L‑9 mapping population at seedling stage - Sock, M.; Diouf, D.; Amoah, N.K.A; Bok‑Lee, S.; Manneh, B.; Bimpong, I.B. (2025)
Abstract Rice (Oryza sativa L) is one of the most important staple food worldwide with a global production estimated at around 800 million metric tons for paddy rice in 2021. However, this production is hampered by several factors, such as land salinity. In this study, 230 F2:3 lines of the Sahel 328/NERICAL-9 mapping populations were evaluated for their tolerance to salinity at the young seedling stage at an electrical conductivity (EC) equivalent to 12 dSm−1. All parameters investigated were negatively affected under saline conditions compared to the control. Of these lines, 10 had a salt injury score (SIS) lower than that of the tolerant control, FL478 and 17 than the donor parent NERICA-L-9. About 4684 informative SNPs and 230 lines were used to construct the genetic linkage map. Twenty quantitative trait loci (QTLs) with LOD>3 that were related to SIS, root length, and shoot length were identified in this study. Twelve new QTLs associated with salt tolerance, qLR2.1, qLR2.2, qLR3.1, qLR3.2, qLR3.3, qLR5, qLR7.4, qLR10, qLR11, qLF6, qSES10 and qSES12, located on chromosomes 2, 3, 5, 7, 10, 11 and 12, respectively were discovered in this study. These QTLs were mapped on the 12 linkage groups (LG), with LG9 having the lowest number of molecular markers (160 SNPs), while LG2 was the largest with 498 markers. These markers may be useful in rice breeding programs.